2017
DOI: 10.1002/slct.201700533
|View full text |Cite
|
Sign up to set email alerts
|

Au Nanorod: An Efficient Catalyst for One‐Pot Synthesis of 3,4‐Dihydropyrimidin‐2(1H)‐ones via the Multicomponent Biginelli Reaction.

Abstract: Gold nanoparticle catalysts have attracted much attention due to their catalytic efficiency under mild conditions. We report here the synthesis of a series of shapes of gold nanocrystals by simple reduction of HAuCl4⋅3H2O and application them as the catalysts for multicomponent Biginelli reaction. Amongst these, unsupported gold nanorods show the best catalytic activity. Its efficiency allows one‐pot synthesis of 3,4‐dihydropyrimidin‐2(1H)‐ones to proceed in high yield under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…A comparison of the results and conditions developed in this work for the synthesis of DHPM 4 a with those from others studies reported in the literature is shown in Table 3 [22][23][31][32][33][34]. It can be highlighted that the catalyst developed in this work promoted the synthesis of DHPM 4 a with a better yield and in a much shorter time than those used in the reactions catalysed by CuHAp 3 , CuSO 4 .5H 2 O and PS-PEG-SO 3 H (Table 3, entries 1, 2 and 3).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…A comparison of the results and conditions developed in this work for the synthesis of DHPM 4 a with those from others studies reported in the literature is shown in Table 3 [22][23][31][32][33][34]. It can be highlighted that the catalyst developed in this work promoted the synthesis of DHPM 4 a with a better yield and in a much shorter time than those used in the reactions catalysed by CuHAp 3 , CuSO 4 .5H 2 O and PS-PEG-SO 3 H (Table 3, entries 1, 2 and 3).…”
Section: Resultsmentioning
confidence: 89%
“…However, it is noteworthy that our methodology used a lower temperature of 80°C (Table 3, entry 6). [23] Finally, in the study of Nguyen, [34] Au nanorod was used as a efficient catalyst for the Biginelli reaction. The DHPM 4 a was obtained with 92% yield, in 1 h of reaction at 100°C.…”
Section: Resultsmentioning
confidence: 99%
“…The three type of Au nanoparticles (nanosheres, nanostars and nanorods) have been reported for the Biginelli reaction . The model Biginelli reaction examined between 1 (1 mmol ), 3 (1 mmol ) and 5 (1 mmol ) in the presence of 1 mL Au colloid at 80 & 100 °C in ethanol.…”
Section: Heterogeneous Catalystmentioning
confidence: 99%
“…Tran and co-workers reported the first use of unsupported Au nanorods to catalyze the Biginelli reaction [ 35 ]. The authors prepared gold nanoparticles in different shapes, such as nanospheres, nanorods and nanostars and developed the Biginelli MCR with the gold nanorods.…”
Section: Gold-catalyzed Multicomponent Reactionsmentioning
confidence: 99%